Reaction pathways for pyridine adsorption on silicon (0 0 1) - Bennett, J.; Marks, Nigel; Miwa, J.; Lopinski, G.; Rosei, F.; McKenzie, D.; Warschkow, O. (Institute of Physics Publishing, 2015)
Density functional theory is used to describe the reactions of chemisorption of pyridine on the silicon (0 0 1) surface. Adsorption energies of six relevant structures, and the activation energies between them are reported. We consider in detail the dative to tight-bridge transition for which conflicting results have been reported in the literature, and provide a description of the formation of inter-row chains observed in high-coverage experiments. We demonstrate that the choice of DFT functional has a considerable effect on the relative energetics and of the four DFT functionals considered, we find that the range-separated hybrid ωB97X-D functional with empirical dispersion provides the most consistent description of the experiment data.